Communication without Communication - Bratina, Boris R.; Knežević, Višnja D. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This paper analyses the necessary conditions for successful communication. It is well known that postmodernity, described as an era of control, produces only decentralized, imploded subjectivities, who are neither able to question their own being nor to relate one with another in authentic bonds of communication. Today, virtual communication has become an ultimate model of every possible communication whatsoever. The authors, therefore, pose the question of conditions for possibility of subjectivities who would be able and apt for authentic communication, wherein faith, fidelity, truth and capability of keeping one's word occupy the central place.
Keywords: subjectivity; fidelity; faith; truth; word; system; post-modernity; communication